Runaways. 3, that was yesterday - Rowell, Rainbow (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2019)
A lot has changed for your favorite super-teens. And a major villain from Runaways past is back in a way you won't be able to predict! The kids have had a hard enough time with a grandma and a 13-year-old, so...things look pretty bleak for everyone in the world. Plus, see a story from a never-before-seen perspective!